Access to micro credit and growth of small small medium enterprises - Linda Nabirye (Uganda Christian University, 2024)
It is, therefore, of utmost importance that development of SMEs takes place for growth and proper development in the different aspects of the Ugandan economy. According to the recent report, one of the most major binding constraints for Ugandan SMEs generally is limited access to finance. This thesis explores the effect microcredit availability has on the growth of small and medium-sized businesses. In this respect, studies have taken into consideration the impact of the microcredit system on the two major categories of employment generation and profitability. The paper identified the determinants of credit availability and its contribution towards growth through an integrated approach of questionnaires and one-on-one interviews with the SME owners and financial institutions. The present research is a cross-sectional one; a total sample of fifty respondents consisting of small company owners, credit institution personnel, and customers participated in the present study. For the purpose of this study, the respondents selected were from government agencies. In the present study, questionnaires have been used for data collection. The ease of access to microcredit facilities has, therefore, been correlated with the growth of small and medium-sized businesses in Uganda. It is also hoped that the owners of small and medium-sized businesses will appreciate the fact that credit facilities have positively contributed to the growth of their companies, and find a solution to the two major challenges-the high interest rates and lack of sufficient collateral-microcredit agencies use in providing credit facilities to SMEs. Since they will be more accessible to microcredit facilities, SMEs will grow more.
Please kindly receive my dissertation